The Impact of Management Policies during the Covid-19 Pandemic Period on Profitability Ratios at PT. Bosowa Berlian Motor Manado Branch - Regina Geraldine Jeremianne; Stanly W. Alexander; Djeini Maradesa (Jurnal Ekonomi dan Bisnis Digital, 2023)
The Covid-19 pandemic has had a major impact on the economic and business sectors. One of the affected business sectors is the automotive sector. Indonesia's wholesale sales for new cars decreased by 48.3% during the first year of the Covid-19 pandemic. This also has an impact on PT. Bosowa Berlian Motor Manado Branch, which experienced a decline in sales and profits. The decline in sales and profits forced the company's management to adopt policies to maximize profits and maintain the continuity of the company during the Covid-19 pandemic. The purpose of this study was to determine the impact of management policies during the Covid-19 pandemic on the profitability ratios at PT. Bosowa Berlian Motor Manado Branch. The research object taken in this study is PT. Bosowa Berlian Motor Manado Branch. The research method used is a qualitative method using profitability ratio analysis. The results of the study show that management policies during the Covid-19 pandemic succeeded in increasing the profitability ratio of PT. Bosowa Berlian Motor Manado Branch.